Effect of straw grass addition as natural fiber on strength and drying shrinkage behaviors of concrete / Huynh Trong Phuoc, Le Van Tua - Huynh, Trong Phuoc
With concerning the sustainable development in the modern constuction industry, this study investigates the effect of adding straw grass as a new type of natural fiber on the strength and shrinkage behaviors of concerte.